El sistema de acreditación de competencia lingüística en la Universidad de Extremadura - Carrasco González, Juan M. (Linguarum Arena, 2018)
We focus on the study of the Portuguese admission test proposed by the Universidad de Extremadura for people over 25 as an example of a foreign language proficiency verification system. We also analyze the mistakes.